PENGARUH SUBSTITUSI TEPUNG KEDELAI DENGAN TEPUNG KAYU APU (Pistia stratiotes) TERFERMENTASI DALAM PAKAN TERHADAP PERFORMA NILA MERAH (Oreochromis sp.) - Gilang Setyawan; Senny Helmiati (Journal of Fish Nutrition, 2021)
Apu wood is a living aquatic plant floating in a lentic water and has a good nutrient content. This study aims to find out the nutrient content of fermented apu wood and evaluate the effect of substitution of soybean flour with fermented apu wood meal in feed on the performance of red tilapia. The study used a randomized design method complete with four substitution treatments of soybean meal with fermented apu wood of 0, 10, 20, and 30% with three repeats. The study used red tilapia measuring 7-9 cm to feed a dose of 3% biomass with a frequency of giving twice a day and maintained for 60 days. Parameters evaluated include sintasan, growth, feed conversion rate, protein efficiency ratio, and feed efficiency. The results of the fermented wood meal proxy test contained water content of 8.80%, protein by 15.10%, fat by 3.12%, ash content by 34.5%, and fiber by 33.96%. Fermented apu wood meal cannot substitute soybean meal as a feed material. Substitution of soybean meal with fermented apu wood meal in feed does not affect the intensity, feed efficiency and protein efficiency ratio but has an effect on decreasing growth performance and increasing the value of feed conversion rate.